PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE DALAM KETERAMPILAN MENULIS KARANGAN DESKRIPSI BAHASA JERMAN SISWA KELAS XI IPS 2 SMA NEGERI 1 MOJOSARI - YUNI MUKTI D., EKA (LATERNE, 2016)
Writing skills in a foreign language is the most difficult skill in learning. The students of SMA Negeri 1 Mojosari have difficulty in finding the ideas to write, especially in writing description. Therefore, the teachers as a central component in learning process need to be creative and innovative. To help the students, then one model of learning that can be applied is round table cooperative learning model. This learning model was applied, because the round table requires all students in the group to write down his ideas in turn. Then a collection of ideas developed to make a description individually, so that this model can help students overcome difficulties. The problem of this research is ?How is the process of implementating the round table cooperative learning model in descriptive writing skills in German language of class XI IPS 2 SMA Negeri 1 Mojosari??. The purpose of this research is ?To know the process of implementating the round table cooperative learning model in descriptive writing skills in German language of class XI IPS 2 SMA Negeri 1 Mojosari.?. The theory used in this research is the theory of Kagan and McCafferty about the round table. The kind of this research is qualitative descriptive. The source of data is based on the research of 32 students of class XI IPS 2 SMA Negeri 1 Mojosari. Data in this research is data process of the implementation the round table cooperative learning model for five meetings. There is also data about learning outcomes in writing description of German language using the round table cooperative learning model as supporting data. The results showed that the round table cooperative learning model has been well implemented according to the correctly procedures. The result of the observation showed that the students became more active during the learning process. The students came to like learning German language with round table cooperative learning model, especially in writing. The German writing skill of the students increased significantly. This is supported by the increase of the students? writting exercise score, although there were still some grammatical errors in writing. So, it can be concluded that round table cooperative learning model can be used as an alternative in learning German language, especially in the teaching of writing skills. Keywords: Writing skills, Descriptions, Models of round table cooperative learning